2019
DOI: 10.1177/0003122419833386
|View full text |Cite
|
Sign up to set email alerts
|

Low-Income Black Mothers Parenting Adolescents in the Mass Incarceration Era: The Long Reach of Criminalization

Abstract: Punitive and disciplinary forms of governance disproportionately target low-income Black Americans for surveillance and punishment, and research finds far-reaching consequences of such criminalization. Drawing on in-depth interviews with 46 low-income Black mothers of adolescents in urban neighborhoods, this article advances understanding of the long reach of criminalization by examining the intersection of two related areas of inquiry: the criminalization of Black youth and the institutional scrutiny and puni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
71
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(73 citation statements)
references
References 68 publications
2
71
0
Order By: Relevance
“…These findings extend prior research indicating worse physical and mental health among mothers whose young adult children have been incarcerated(Goldman 2019;Green et al 2006) and women with incarcerated household members. The results also build on recent evidence that Black adolescents' stressful experiences, including arrest and broader criminalization, strain their mothers' well-beingElliott and Reid 2019).It is possible that mothers with incarcerated sons would experience poor health even in the absence of incarceration. Middle-aged women with low socioeconomic status are already at risk of experiencing severe hardship(Willson et al 2007).…”
supporting
confidence: 66%
See 1 more Smart Citation
“…These findings extend prior research indicating worse physical and mental health among mothers whose young adult children have been incarcerated(Goldman 2019;Green et al 2006) and women with incarcerated household members. The results also build on recent evidence that Black adolescents' stressful experiences, including arrest and broader criminalization, strain their mothers' well-beingElliott and Reid 2019).It is possible that mothers with incarcerated sons would experience poor health even in the absence of incarceration. Middle-aged women with low socioeconomic status are already at risk of experiencing severe hardship(Willson et al 2007).…”
supporting
confidence: 66%
“…The effects of sons' incarceration on mothers may also be enduring as sons get into trouble, are incarcerated, return to the community, and in many cases, continue to cycle through the criminal legal system. Even prior to their sons' confinement, mothers may experience shame, stress, and their own criminalization due to their sons' repeated exposure to surveilling institutions (Comfort 2008;Elliott and Reid 2019;Goffman 2014). In addition, young men's heavy reliance on their mothers for court fees and prison expenses is likely a source of distress for mothers, most of whom are already very poor (Braman 2004;DeVuono-Powell et al 2015).…”
Section: Son's Incarceration and The Stress Processmentioning
confidence: 99%
“…For example, Dow's () study of African American mothers showed that the ideology surrounding child care is mother focused but includes expectations that kin and community are a key part of raising children. In contrast, Elliott and colleagues (Elliott et al, ; Elliott & Reid, ) emphasized that low‐income Black mothers feel pressure from having sole responsibility for protecting children from making unwise decisions and getting into trouble, make various efforts to monitor or teach their children, and blame themselves when children cannot succeed. More research that examines aspects of intensive parenting ideology and its felt pressures on parents by race/ethnicity and other social statuses, as well as by geographic region is warranted.…”
Section: Changing Norms Of Parentingmentioning
confidence: 99%
“…These intersecting social structures shape parenting in large part through state governance practices. Mothers, especially mothers marginalized by race and class, are acutely aware that authorities, including CPS, are scrutinizing their parenting, evaluating their motherhood against an ideal that fails to account for the systemic challenges they face (Elliott and Bowen 2018; Elliott and Reid 2019; Fong 2019a; Gurusami 2019). This work documents mothers’ perspectives of the surveillance they encounter, with less attention to the operation and practices of the surveilling systems themselves, calling for research on the mechanisms producing mothers’ fears and systems (dis)engagement.…”
Section: Child Protective Servicesmentioning
confidence: 99%